Long-term outcome of percutaneous vertebroplasty versus conservative treatment for osteoporotic vertebral compression fractures: a retrospective cohort study with three-year follow-up - Chen, Zefu; Xu, Lei; Shi, Liang; Cao, HongXia; Nie, Mingxi (Frontiers in Medicine, 2024)
Background Osteoporotic vertebral compression fractures (OVCF) appear to be more common as the population ages. Previous studies have found that percutaneous vertebroplasty (PVP) can achieve better short-term clinical outcomes than conservative treatment (CT) for OVCF. However, the long-term outcomes of PVP compared with CT for OVCF has been rare explored. This study was designed to explore the clinical outcomes of PVP or CT within 3 years after OVCF. Methods This study reviewed the clinical outcomes of patients who underwent PVP or CT for OVCF in a single center from January 2015 to December 2019. The back pain visual analogue scale (VAS), Oswestry disability index (ODI) and satisfaction rate were compared between the two groups at baseline, 1 week, 1 month, 3 months, 6 months, 12 months, 24 months and 36 months after treatment. Outcomes The baseline data including gender, age, bone mineral density, body mass index, back pain VAS, and ODI were not significantly different between the two groups. The back pain VAS and ODI of CT patients were significantly higher than those of PVP group at 1 week, 1 month, 3 months, 6 months and 12 months after treatment. The satisfaction rate in the PVP group were significantly higher than those in the CT group at 1 week, 1 month, 3 months and 6 months after treatment. Subsequently, the back pain VAS and ODI showed no significant difference between the two groups at 24 and 36 months. In addition, there was no significant difference in treatment satisfaction between the two groups at 36 months. There was no significant difference in the rate of new vertebral compression fractures between the two groups within 36 months after treatment. Conclusion The clinical outcomes within 12 months after PVP and patient satisfaction rate within 6 months after PVP were significantly higher than CT. However, during 12 months to 36 months, this advantage generated by PVP was gradually diluted over time. Compared with CT, the long-term effect of PVP on OVCF should not be overestimated.